A prospective cohort study on survival and success of one‐piece mini‐implants with associated changes in oral function: Five‐year outcomes. Issue 6 (8th May 2019) - Enkling, Norbert; Haueter, Marius; Worni, Andreas; Müller, Frauke; Leles, Cláudio Rodrigues; Schimmel, Martin
Abstract: Objective: To investigate in a prospective cohort study the 5‐year post‐loading survival and success of one‐piece mini dental implants (MDIs) in edentulous subjects with mandibular implant overdentures (IODs) and to report the associated changes of oral function with respect to patient age. Materials and methods: Independently living edentulous patients were recruited and provided with new complete dentures. After an adaptation period, four one‐piece MDIs (diameter 1.8 mm) were installed in the interforaminal region and immediately loaded. At baseline pre‐operative (BL), as well as at 1‐year and 5‐year follow‐up examinations, chewing efficiency was assessed with a validated color‐mixing ability test and maximum voluntary bite force (MBF) was recorded with a digital force gauge. Implant survival and success were evaluated at 5‐year follow‐up. Non‐parametric tests served to analyze the differences between time points. Results: Twenty patients participated in the study (5 men and 15 women; age at BL: n  = 10 ≤ 65 years and n  = 10 > 65 years). All patients were available for a 5‐year follow‐up ( n  = 2 in their long‐term care facility; n  = 1 only by telephone). The survival and success rates were both 100% after 61 ± 5.7 months. Chewing efficiency did not change over the first year ( p  = 0.167), but was improved at 5 year fup ( n  = 19) compared to baseline ( p  = 0.033) and to 1 year ( p  < 0.001). The MBF ( n  = 19 at 5‐year follow‐up) increased continuously over time ( p  < 0.001), but was less pronounced in the older cohort ( p  = 0.009). Conclusions: Mini dental implants seem to be a successful treatment option for edentulous elderly patients with very high survival and success rates, and serve to improve long‐term oral function.